TQM, knowledge management and collaborative commerce adoption: A literature review and research framework - Chong, Alain Yee Loong; Ooi, Keng Boon; Lin, Binshan; Teh, Pei Lee (Taylor & Francis, 2010)
This article discusses the influence of total quality management (TQM) and knowledge management (KM) on collaborative commerce (c-commerce) adoption. An extensive review of literature was carried out to develop an integrated model of TQM and KM to examine the influence of TQM and KM on c-commerce adoption. The findings provide a basis for developing a model to advance the TQM, KM and innovation adoption research literature. This study proposes a new integrated model which includes practices from both TQM and KM theories to examine if these practices will result in an improvement in the adoption of c-commerce. Organisations intending to adopt or increase the level of adoption of c-commerce will be able to make managerial decisions based on TQM and KM practices from this research. The study makes a significant contribution by combining TQM and KM models as a methodological example which is useful for practitioners to track the degree of TQM and KM effects on c-commerce adoption. This model can be used by companies to do a pre-test baseline measurement, and then periodically reassess the effects of any TQM and KM change.